2021
DOI: 10.1037/hea0001048
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-involved sexual aggression: Emotion regulation as a mechanism of behavior change.

Abstract: Objective: Sexual aggression remains a significant public health problem, with the majority of sexual assaults involving alcohol. Founded upon an experimental medicine approach to behavior change, the current study used a proximal change experiment to target and test emotion regulation (ER) as a mechanism underlying alcohol-involved sexual aggression. Method: Heavy episodic drinking men aged 21–30 with a sexual assault perpetration history (N = 209) were randomly assigned to a brief, online, ER-focused cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
2
29
2
Order By: Relevance
“…We seek Here, we also wish to briefly highlight to researchers the personal and situational factors that alcohol likely exacerbates. It is likely that alcohol interacts in important and interesting ways with the psychological processes we describe (e.g., for effects of alcohol on perceptions of sexual interest, see Abby & Ross, 1992;Abbey, Zawacki, & McAuslan, 2000; Jacques-Tiurra, Abbey, Parkhill, & Zawacki, 2007;George, Gournic, & McAfee, 1988; emotion regulation, see Davis, et al, 2020;self-justification, Koss & Cleveland, 1997;George & Marlett, 1986; and labeling of sexual victimization, Orchowski, Untied, & Gidycz, 2013). We especially welcome future work that examines these interactions.…”
Section: Three Things Our Story Omitsmentioning
confidence: 91%
“…We seek Here, we also wish to briefly highlight to researchers the personal and situational factors that alcohol likely exacerbates. It is likely that alcohol interacts in important and interesting ways with the psychological processes we describe (e.g., for effects of alcohol on perceptions of sexual interest, see Abby & Ross, 1992;Abbey, Zawacki, & McAuslan, 2000; Jacques-Tiurra, Abbey, Parkhill, & Zawacki, 2007;George, Gournic, & McAfee, 1988; emotion regulation, see Davis, et al, 2020;self-justification, Koss & Cleveland, 1997;George & Marlett, 1986; and labeling of sexual victimization, Orchowski, Untied, & Gidycz, 2013). We especially welcome future work that examines these interactions.…”
Section: Three Things Our Story Omitsmentioning
confidence: 91%
“…The empirical literature has found an association of anger and sexual assault perpetration in both cross-sectional and experimental methodologies (Davis, 2010; LeBreton et al, 2013; Thomas & Gorzalka, 2012). Perpetrators of sexual assault report higher trait anger than nonperpetrators (LeBreton et al, 2013), and in-the-moment anger (e.g., state anger) is associated with intentions to perpetrate sexual assault (Davis et al, 2020; Thomas & Gorzalka, 2012). Evidence suggests alcohol may facilitate sexual assault perpetration by exacerbating trait anger (Shorey et al, 2017) or directly increasing negative emotions, such as anger (Davis, 2010).…”
Section: Alcohol As a Predictor Of Sexual Aggressionmentioning
confidence: 99%
“…One recent study examining state ER found men with histories of sexual assault perpetration reported difficulties modulating emotions during a hypothetical sexual assault scenario (Davis et al, 2020). Moreover, in the moment, access to strategies to modulate emotions (one facet of state ER) was associated with decreased intentions to perpetrate sexual assault (Davis et al, 2020). Further research is needed to understand the association between state ER and sexual assault perpetration, particularly in the context of established predictors of sexual aggression, such as acute intoxication and anger.…”
Section: Alcohol As a Predictor Of Sexual Aggressionmentioning
confidence: 99%
“…Despite the rise in web‐based recruitment, hard copy flyers placed in relevant community settings, and tailored to the population of interest still have utility. For example, in a study recruiting young adults who consume alcohol (Davis et al., 2020), flyers placed in local bars were effective. Similarly, placing flyers in wig shops set up especially for cancer patients has helped us reach breast cancer survivors (Larkey et al., 2015).…”
Section: Strategies For Effective Recruitmentmentioning
confidence: 99%